Implementasi Konsep Sparkling Spring pada Perancangan Interior Belle Ballet School di Surabaya - Yovina Marselia (Intra, 2016)
School is a place where kids can get an education. Generally kids spends 12 hours of their day in school and that can make them feel tired and bored. Interior planning for Belle Ballet School can help kids to develop their talent in ballet, so they can distribute their boredom during long hours in their school. Belle Ballet School will be redesigned byproviding more facilities, more interesting and fun ambience that can make people feel cozy inside it.Belle Ballet School is designed for kids to develop their ballet with a concept of playing while learning, so that the school ambience will be cheerful. The design concept for this school is “Sparkling Spring” that can give a cheerful ambience in school interior and can pop out children’s passion in ballet and the school itself (Belle Ballet School).